2021
DOI: 10.3389/fimmu.2021.661911
|View full text |Cite
|
Sign up to set email alerts
|

PSMP Is Discriminative for Chronic Active Antibody-Mediated Rejection and Associate With Intimal Arteritis in Kidney Transplantation

Abstract: Chronic active antibody-mediated rejection (CAAMR) is an intermediate process that occurs during the development of chronic antibody-mediated rejection (CAMR), which is a key problem associated with the long-term kidney grafts survival. This study investigated the role played by PC3-secreted microprotein (PSMP) in the progression of CAAMR and CAMR. We showed that CAAMR and CAMR patients’ allografts dysfunction with declined survival rate, which suggested that earlier diagnosis and treatment of CAAMR might be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Another study found that PSMP secreted by ovarian cancer cells induced by hypoxia could promote angiogenesis through the MAPK signaling pathway (128). In addition, the expression level of PSMP in patients with chronic active antibody-mediated rejection (CAAMR) has been enormously increased, and there is a significant correlation with the number of infiltrating CD68 + macrophages (129). We found that IL-1b, damage-associated molecule pattern (DAMP) molecules IL-33 and HMGB-1 could induce mouse primary hepatocytes to produce PSMP (32).…”
Section: Psmp In Liver Diseasementioning
confidence: 99%
“…Another study found that PSMP secreted by ovarian cancer cells induced by hypoxia could promote angiogenesis through the MAPK signaling pathway (128). In addition, the expression level of PSMP in patients with chronic active antibody-mediated rejection (CAAMR) has been enormously increased, and there is a significant correlation with the number of infiltrating CD68 + macrophages (129). We found that IL-1b, damage-associated molecule pattern (DAMP) molecules IL-33 and HMGB-1 could induce mouse primary hepatocytes to produce PSMP (32).…”
Section: Psmp In Liver Diseasementioning
confidence: 99%
“…2,3 In particular, mechanisms controlling antibody-mediated rejection (AMR) are poorly understood, resulting in a paucity of specific therapeutic treatments. 4,5 Most inflammatory and regulatory adaptive immune responses after transplantation have been thought to be generated in secondary lymphoid organs. However, newer paradigms suggest that proinflammatory and regulatory alloimmune responses can also be generated and regulated locally within the graft.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that CCN1 knockdown increased levels of MSMP. The functions of MSMP have not been fully elucidated although it can act as a chemoattractant for macrophages [38]; the latter study indicated that MSMP is a chemokine ligand for the receptor CCR2. MSMP is up-regulated in prostate cancer cells in hypoxic conditions, resulting in increased drug resistance [39].…”
Section: Identification Of Proteins Differentially Expressed After Cc...mentioning
confidence: 99%